Effect of Agnikarma with Tapta Guda in Carpal Tunnel Syndrome- A Case Study (International Journal of Ayurveda and Pharma Research, 2022)
Carpal tunnel syndrome (CTS) is the most common entrapment neuropathy of upper extremity. It affects approximately 3% of the general adult population in the world. Women are three times more likely to have CTS than men. In conventional system, medications such as corticosteroids, Non-Steroidal anti-inflammatory drugs, etc., are used in management of carpal tunnel syndrome. Surgical decompression of carpal tunnel is the main stay of treatment for CTS. The structures involved in carpal tunnel is mainly the tendons, ligaments and nerves which can closely related with Snayu, thus Carpal tunnel syndrome can be correlated with Snayugata vata affecting Manibandhasandhi. Dahanopkarana used for Vatavyadi affecting Snayu, Sandhi, Asthi are Kshaudra, Guda, Sneha. Agnikarma with Snigdha dravyas have more penetrating capacity than Rooksha dravyas like Shalaka. So, Taptaguda is taken in the present study to assess the effect of Agnikarma in carpal tunnel syndrome. Here the patient was treated with Agnikarma using Taptaguda over the most painful and tender points. Assessments were done before treatment, after treatment, 7th day, 15th day and 30th day. The result showed Agnikarma with Taptha guda was effective in treating Carpal tunnel syndrome